Analysis of Determinants of Sustainability of MSMEs in the Tourism Sector of Kerinci Regency - Sari, Deby Anggun; S, Liona Efrina; Hartati, Bella; Irawan, Deki (Universitas Batanghari Jambi, 2025)
This study aims to analyze the factors that influence the income of MSME traders in the tourism sector in Kerinci Regency, and analyze the prospects for the sustainability of MSMEs in the tourism sector in Kerinci Regency. The first analysis method used is multiple linear regression data analysis, the multiple linear regression model is used to measure the influence of independent variables, namely capital, working hours, length of business, labor and education on the dependent variable, namely MSME income, and secondly, Multidimensional Scaling (MDS) analysis is used, to analyze the prospects for the sustainability of MSMEs in the tourism sector in Kerinci Regency. The results of this study concluded that simultaneously the variables of capital, working hours, business duration, and labor have a positive and significant influence on the income of traders. However, partially only the labor variable does not have a significant effect on the income of MSME traders in the tourism sector in Kerinci Regency. This study also concluded that the analysis of the sustainability of tourism sector businesses in Kerinci Regency was obtained multidimensionally with a fairly sustainable category for MSMEs in the tourism sector in Kerinci Regency.